Kajian Etnobotani Tumbuhan Obat Untuk Penyakit Malaria pada Masyarakat Kabupaten Keerom - Fitriah Ardiawijianti Iriani; Rosita Irianti Dehi; Alpha Christyananda Damar (Pusat Riset dan Inovasi Nasional, 2025)
Malaria remains a major public health problem in Papua, including Keerom District. Limited access to healthcare services has encouraged the local community to utilize traditional medicinal plants as an alternative therapy for malaria. This study aimed to document local knowledge regarding the use of antimalarial medicinal plants in Arso 7, Keerom District.The study was conducted in October 2023 using a descriptive qualitative design. The study population consisted of 500 households, with a purposive sample of 100 households. Primary data were collected through field observations, in-depth interviews using semi-structured questionnaires, documentation, and plant collection for botanical identification. Secondary data were obtained from relevant institutions and literature. Data were analyzed qualitatively by categorizing plant species based on local names, scientific names, plant parts used, preparation methods, and medicinal properties, and were presented descriptively.The findings revealed that the majority of respondents were aged 36–45 years (38%), female (68%), had primary school education (59%), and worked as housewives (51%). The most commonly used plants were papaya (Carica papaya) (45%), sambiloto (Andrographis paniculata) (40%), and brotowali (Tinospora crispa) (11%). Most plants were sourced from home gardens (60%), used in fresh form (100%), with leaves being the most frequently utilized part (98%), and predominantly prepared by boiling (90%).This study highlights that the traditional use of medicinal plants for malaria treatment remains strong within the Keerom community. Documenting this ethnobotanical knowledge is essential for preserving local wisdom and supporting the development of safe and sustainable antimalarial remedies.